#TITLE_ALTERNATIVE# - Bakrie (NIM 25395020), Muhammad
ABSTRACT: Lead (Pb) is one of toxic metal used widely as raw material in industries. Lead concentrations of 0 mg/I to 400 mg/1 have been reported from some of the proceeding industrial sources. In Indonesia, lead is mostly removed from solution by chemical precipitation. However, this method generates sludge that is not easily handled. One of effective and recoverable alternatives to remove lead is cementation utilizing iron spheres, and it is capable for effluent with Pb concentration less than 5 g/l. The disadvantages of cementation process is at low pH, therefore it caused excess in iron consumption. The objectives of research are to study processes and kinetics of lead removal, to determine effectiveness, to minimize iron concentration, and to determine mathematics model to predict process-rate. Lead removal is done both in batch and continuous reactor at room temperature and aerobic condition. The variables are initial concentrations of Pb, flow rate, pH and length of beds. The experimental data were analyzed statistically, and mass-transfer rate in empiric equation form are correlated to variables that control flow charac-teristic and were compared with literature data. And then, lead removal efficiency was tested using dry ingot (cell-battery) manufacture wastewater. The results showed that cementation Pb-Iron reaction is first order reaction. Increase of initial concentration of Pb doesnt give much effect to value of reaction rate constant and lead ion percentage removal (LPR) and give much effect to decreasing of iron consumption coefficent (ICC). Optimum LPR and ICC were obtained at pH=3. Flow rate increase could decrease LPR and ICC, while increase of length of bed could increase LPR and ICC. Empiric model on cementation Pb-iron system was expressed as Jp (0,5058 / e) Re -0,407 this model can be used to predict process-rate. From ingot manufacture wastewater test, lead removal percentage was 89,5%, otherwise lead removal predicted by model is less 3.3% than that values. The following research is needed to find recovery method of cementation Pb and to prevent clogging on bed.